Farysizyma gen. nov., an anamorphic genus in the Ustilaginales to accommodate three novel epiphytic basidiomycetous yeast species from America, Europe and Asia - Fonseca, Álvaro (2010)
FEMS Yeast Research, Vol. 8, Nº 3